2010
DOI: 10.1002/ar.21320
|View full text |Cite
|
Sign up to set email alerts
|

The Atrioventricular Region of the Teleost Heart. A Distinct Heart Segment

Abstract: This article reports the morphological characteristics of the atrioventricular (AV) region of the teleost heart. A total of 29 teleost species belonging to 19 families and 10 orders were analyzed. The study includes hearts with entirely trabeculated ventricles and hearts possessing a ventricular compacta. In all cases, the AV region is formed by a ring of compact myocardium surrounded by a connective tissue ring. The myocardium contains vessels in most species having entirely trabeculated ventricles, and in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 28 publications
1
32
0
1
Order By: Relevance
“…Areas of continuity with the atrial and ventricular muscle are always observed (Fig. 2.7 ) (Icardo and Colvee 2011 ) . From a morphological point of view, the AV region constitutes a distinct segment of the adult teleost heart.…”
Section: The Atrioventricular Regionmentioning
confidence: 94%
See 4 more Smart Citations
“…Areas of continuity with the atrial and ventricular muscle are always observed (Fig. 2.7 ) (Icardo and Colvee 2011 ) . From a morphological point of view, the AV region constitutes a distinct segment of the adult teleost heart.…”
Section: The Atrioventricular Regionmentioning
confidence: 94%
“…Strikingly, this feature is not restricted to temperate teleosts. Coronaries are also observed in the Antarctic species Dissostichus mawsoni (Icardo and Colvee 2011 ) and Nothotenia angustata (Eastman 1993 ) . Overall, ventricular subepicardial vessels are not very numerous, and they do not appear to form a very rich plexus.…”
Section: The Ventriclementioning
confidence: 98%
See 3 more Smart Citations